Staphylococcus Epidermidis Producteur D’entérotoxine C Impliqué Dans Une Septicémie À Foyer Urinaire - Chimène Nadège Mahoussi Nanoukon; Euloge Gbètondji Dassou; Marcos Dousso; Frédéric Sogbo; Haziz Sina; Gilles Prevost; Lamine Baba-Moussa (European Scientific Journal, ESJ, 2017)
In developing countries, coagulase-negative staphylococcal (SCN) infections are often neglected. Here, we describe the identification of a coagulase-negative staphylococcal strain secreting type C staphylococcal enterotoxin (SEC) in a field weakened by severe malaria in a 12-year-old child and summarize the clinical characteristics of the patient. The identification of the strain is carried out by MALDI-TOF mass spectrometry after protein extraction. The toxigenic capacity of the species in question is determined by the polymerase chain reaction (PCR) and the radial immunoprecipitation method. The patient's medical record was used for the study of the correlation between the clinical phenotype of the patient and the production of SEC by the strain. S. epidermidis was identified as the pathogen responsible of bacteremia which induces clinical sepsis, hematemesis and thrombocytopenia. The PCR test revealed that the isolated strain was positive for sec gene and its expression was confirmed by the radial immunoprecipitation assay. The study of the patient's medical record shows that the enterotoxin produced by the strain may have contributed to the severity of the clinical picture with the presence of disseminated intravascular coagulation stigmata (DIC) in a context of sepsis with a urinary starting point. These data suggest that CNS infections may be underestimated due to difficulties in species identification and the toxigenic capacity of some of these isolates.